Peran Kepemimpinan Kepala Desa Terhadap Pembangunan di Desa Ciangsana Kecamatan Gunung Putri Kabupaten Bogor - Salsabila Ramadanti; Evi Priyanti (Universitas Muhammadiyah Sumatera Utara, 2023)
The village head's leadership in the community cannot be separated from the success of village development, this is also the responsibility of the local government, namely the task of development. The success of village development depends on the support of the entire community, and is greatly influenced by the role of the parties who are coordinators of development implementation. In order to use their role effectively and really contribute to the development process in this situation, governments must be able to form several governmental units. This study aims to determine the role of village heads in infrastructure development in Ciangsana Village, Gunung Putri District, Bogor Regency. This research methodology is descriptive qualitative. The findings of the idea study support that village leaders are essential for community development. Other responsibilities of village heads include inspiring, facilitating, and generating new ideas for local development initiatives. Evidently, village heads actively participate in building village infrastructure for the benefit of their environment.Keywords: The Role of the Village Head, Development, Community Participation